Análise evolutiva de genes de homeostase de ferro e de elementos repetitivos em espécies modelo - Victoria, Filipe de Carvalho (2011)
Iron is an essential element for plant development, involved in metabolic processes, such respiration and photosynthesis. However, data regarding the genotype by environment interaction are lacking. Comparative analysis with lower plant groups and crop plants can increase the understanding about these processes. The use of bryophytes as model plants rise as a promising strategy since they present simpler patterns of development. The present work aimed to identify the occurrence patterns of molecular markers in model plant species, as well as to infer about the phylogenetical relationships of gene families related with iron homoestasis in plants, allowing the development of tranfer strategies of genomic data across model and orphan species. Using bioinformatics tools, a survey analysis was performed to detect repetitive elements in EST banks of eleven plant species. To validate the SSR markers found, 100 primer pairs were developed on the microsatelite sequences obtained for Physcomitrella patens Brid. and tested against genomic DNA of Polytrichum juniperinum Hedw. Phylogenetic and divergence time analysis was performed for the gene families Iron Regulated Transporter (IRT), Ferric Redectase Oxidase (FRO), Nicotinamide synthase (NAS), Yellow Stripe-Like (YSL) and Natural Resistance-Associated Macrophage Protein (NRAMP), related to the iron homoestasis, with help of the Bayesian inference and using the rice, Arabidopsis and P. patens genes for the Blast search in distinct land plants species. Also, primers for transposable elements recognizably related to Ysl genes were developed and applied jointly with the SSR primers by the IRAP/REMAP technic searching to find microsatellite markers associated to copies of this gene family. A total of 13,133 SSR markers were discovered in non- redundant EST databases made for all eleven species chosen for this study. The dimer motifs are more frequent in lower plant species, such as green algae and mosses, and the trimer motifs are more frequent for the majority of higher plant groups, such as monocots and dicots. Thirty percent of EST-SSE were successfully transferred with a relative polimorphism information across Physcomitrella patens Brid. and P. juniperinum, being promising for mapping and comparative genome analyses in plants. A total of 243 iron uptake gene sequences for 30 plant species were found using rice and Arabidopsis thaliana (L.) Heynh. homologues as queries. The evolutionary fingerprinting analyses suggested a positive selective pressure on iron uptake genes for most of the plant homologues analyzed, enabling an optimization and maintenance of gene function. The divergence time analysis indicates IRT as the most ancient gene family and FRO as the most recent. NRAMP and YSL genes appear as a close branch in the evolution of iron uptake gene families. No recent duplication in grasses were found based in the bayesian inference, and paralogue copies were only observed for dicot species. The Nramp cis-acting homology search indicated an ancestral duplication hypothesis for this gene family in grasses. Using IRAP/REMAP techniques, it was observed that YSL homologues in Physcomitrella are surrounded by copia-like retrotransposons as occurs in the maize ZmYSL1 copy. Also Polytrchum juniperinum Hedw. in vitro cultures were estabilished using spores as explants. Protonemal and gametophyte development were obtained using a growth regulator free culture medium.